The Increasing Role of Kappa Free Light Chains in the Diagnosis of Multiple Sclerosis - Franz Felix Konen (MDPI AG, 2021)
Free light chains (FLC) are a promising biomarker to detect intrathecal inflammation in patients with inflammatory central nervous system (CNS) diseases, including multiple sclerosis (MS). The diagnostic use of this biomarker, in particular the kappa isoform of FLC (“KFLC”), has been investigated for more than 40 years. Based on an extensive literature review, we found that an agreement on the correct method for evaluating KFLC concentrations has not yet been reached. KFLC indices with varying cut-off values and blood-CSF-barrier (QAlbumin) related non-linear formulas for KFLC interpretation have been investigated in several studies. All approaches revealed high diagnostic sensitivity and specificity compared with the oligoclonal bands, which are considered the gold standard for the detection of intrathecally synthesized immunoglobulins. Measurement of KFLC is fully automated, rater-independent, and has been shown to be stable against most pre-analytic influencing factors. In conclusion, the determination of KFLC represents a promising diagnostic approach to show intrathecal inflammation in neuroinflammatory diseases. Multicenter studies are needed to show the diagnostic sensitivity and specificity of KFLC in MS by using the latest McDonald criteria and appropriate, as well as standardized, cut-off values for KFLC concentrations, preferably considering non-linear formulas such as Reiber’s diagram.